BeBieF mit der Technologie: The Learning of German Speaking - Primardiana Hermilia Wijayati; Anggi Novitasari (Future Science, 2024)
BeBieF mit der Technologie is learning that integrates technology and utilizes virtual space to prepare learners for metaverse learning. Virtual space combines high-level communication by utilizing internet applications with several types of technology to complete tasks. The technology integration in this study uses Zoom Video Conferencing, Skype, and WhatsApp Voice note which are applied in the form of monologue and dialogue assignments related to the topic of Hobby/Freitzeitbeschäftigung. This article aims to describe the the implementation of BeBieF mit der Technologie as innovative German language learning in developing learners' speaking skills. Data were collected through speaking assignments and questionnaires. The data were then analyzed using descriptive quantitative method. The research subjects were 54 learners of class XII semester I. The results of the data analysis showed that 77% of learners had very good task fulfillment/completion and 60% of learners had very good pronunciation. The application of BeBieF mit der Technologie reveals the strengths and weaknesses of students in speaking skills. The application of BeBieF mit der Technologie is fun and interesting so that learners can understand and use everyday expressions with simple sentences based on the topic.